National University Extension and Its Impact on the Development of Rural Communities: Contributions to Self-Managing Development of Barra de Colorado Community in Pococi, Limon, Costa Rica - Arboleda-Julio, Esteban (2016)
As part of the process of extension of the National University (UNA) School of Agricultural Sciences (ECA) participated in a project which was implemented jointly University of Costa Rica (UCR), the State Distance University (UNED) and the Technological Institute of Costa Rica (ITCR). This project was funded by CONARE as part of an initiative for regional development. ACE itself was mainly participating in the participatory formulation of the Local Development Plan 2011-2016 of the community of Barra de Colorado, district of Barra de Colorado, Pococí province of Limon. This Development Plan became a tool that allowed the community to the negotiation of resources and services to public institutions, it can open opportunities and benefits have always been long cherished by the families of the community, as they have always been in condition of marginalization, exclusion and neglect of the benefits of the municipality and most state institutions, this is certainly one of the main causes of the high rate of poverty in the community, because there is no access to Basic services institutions and stable sources of employment, which does not allow families to improve their quality of life, this results that the community of Barra de Colorado this among the five poorest districts of the country, as we It reflects the Social Development Index of 15.9 according to MIDEPLAN, 2007. The Development Plan of the Community of Barra del Colorado, consists of a participatory assessment on the status of the strategic sectors of the community. A comprehensive analysis of the situation of the community is then performed, then projecting the situation of the community, to do this two scenarios are built over time is performed: Pessimistic and optimistic. The vision of development to be achieved (the principles and integrated, mission, objectives) is projected. A series of strategic components are then established (within which the projects required to solve the problems that limit the development of families in the canton are established). Finally, the implementation strategy of the plan and participatory monitoring, where community organizations should participate, the municipality, state institutions, public universities and other bodies established, which in a coordinated manner to perform management solutions to the problem which has prevented the development of families in the community of Barra de Colorado. To make this process management, implementation and evaluation of the Development Plan, the proposed set to CONARE Interuniversity Development Initiative Huetar Atlantic Region, which ensures taken as a basis for a specified time with the advice that has so far provided School of Agricultural Sciences, National University (UNA), the participation of the State Distance University (UNED), the University of Costa Rica (UCR) and the Costa Rica Institute of Technology. (ITCR), likewise, the community organization of Barra de Colorado should continue to undertake the management of the Development Plan which should promote and realize a whole work for coordination and other inter-governmental organizations and civil society entities to integrate economic, human and logistical efforts to achieve the goals set in the Development Plan.